Cardiovascular risk factors and proteinuria in Toba aborigines from Chaco, Argentina - Bianchi, María Eugenia Victoria; Cusumano, Ana María; Velasco, Gustavo Adolfo (Kidney International, 2013)
The Province of Chaco (Argentina) was part of the ‘Great Chaco’, a geographical region of area 300,000km2, which comprised the North East of Argentina, the South East of Paraguay, and Bolivia. Since ancient times, the region has been inhabited by aborigine ethnic groups. At present, aborigines constitute 4.8% of the Province inhabitants.
Keywords: Chaco (Argentina); Cardiovascular; Toba aborigines